Study of the Properties of Coconut Fiber to explore Suitability to be used in Reinforced Concrete - Joshi, Khem Raj; Mandal, Bharat; Ghoshal, Tarumay (Nepal Journal of Science and Technology, 2023)
Natural fibers have been utilized in construction materials consistent with the concept of sustainability. These fiber sources are abundant in many parts of the world. It is established that the orientation of coconut fiber used in concrete mix, attempt to obtain the highest possible ductility as opposed to normal brittle nature of concrete. However, alternative binders must also be utilized in an effort to prolong the useful life of these plant fibers in composite to increase the tension capacity of concrete. The use of these fibers increases tension capacity of that concrete and reduces negative environmental consequences. Coconut fibers are generally economic and present in abundance thus making it a possible choice for use as a concrete reinforcement material. Therefore, in this study, physical as well as mechanical properties of coconut coir have been evaluated to explore the use of it as favorable concrete reinforcing fiber. It is found that coconut fibers have 0.2 to 0.4 times tensile strength of mild steel. Similarly, its elongation property against mild steel is near about 0.3 times before breaking. The other major property, bonding with concrete is also found comparable to bond of reinforcement with concrete. The Non-toxic and environmental friendly properties are particularly additional advantages on the use of such bio composites in concrete.